Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage dan Opini Auditor Terhadap Audit Report Lag Pada Perusahaan Sub Sektor Hotel, Restoran, dan Pariwisata Yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2020 - Florencia Eleazar, Monica; Ratih, Suklimah (Rifa'Institute, 2022)
Hotel, restaurant, and tourism sub-sector based on the conditions that occur. Reporting from one of the news sources found, it has provided information that since the beginning of the Covid-19 outbreak in Indonesia, the hotel, restaurant and tourism sub-sector was one of the most affected sub-sectors with losses reaching Rp. 85.5 trillion. This study aims to determine the effect of firm size, profitability, leverage, and auditor's opinion on Audit Report Lag in hotel, restaurant, and tourism sub-sector companies listed on the Indonesia Stock Exchange in 2017 – 2020. This study uses a quantitative approach research method, the number of samples used in this study as many as 13 companies using purposive sampling technique. The results show that (1) company size partially has no effect on Audit Report Lag, indicating that the size of the company's size does not affect the duration of the process of preparing audit financial statements, (2) profitability partially has a negative and significant effect on Audit Report Lag. indicates that companies getting large profits will be faster in the process of preparing audited financial statements so as to reduce Audit Report Lag, (3) partial leverage has a positive and significant effect on Audit Report Lag indicating that companies that have high levels of debt then the risk of the company will large and this affects the process of completing the audit financial statements so that the process will take longer, and (4) the auditor's opinion partially has no effect on the Audit Report Lag indicating a company that received an unqualified opinion. Qualified opinion or opinion other than unqualified opinion does not affect the process of preparing the audited report.